Ultrasound-guided foam sclerotherapy of great saphenous vein with 2% polidocanol – one-year follow-up results - Jacek Kurnicki; Marcin Osęka; Robert Tworus; Zbigniew Gałązka (Videosurgery and Other Miniinvasive Techniques)
Introduction : Ultrasound-guided foam sclerotherapy (UGFS) of varicose veins is a useful treatment option. It is a relatively safe method in the case of limited, small varicose veins. In theory, a justified concern could be raised that the injection of an active drug into the large superficial venous vessels may potentially cause life-threatening consequences. Aim : To assess the safety and efficacy of UGFS using a 2% solution of polidocanol (Aethoxysklerol 2%) in the case of great saphenous vein incompetence. Material and methods : Fifty-two patients with great saphenous vein incompetence underwent ultrasound-guided foam sclerotherapy. The efficacy criterion was the elimination of reflux measured ultrasonographically and withdrawal or decrease of complaints: 1 week, and 1, 3, 6 and 12 months after the treatment. Complications of sclerotherapy were reported during follow-up. Results : Decrease or withdrawal of complaints of chronic venous insufficiency was reported in 96% of cases (50 patients). Disappearance or decrease of varicose veins was noted in all patients (100%). During examination after 12 months, full success of ultrasound was achieved in 38 (73%) cases, and 11 (21%) patients presented a partial desired effect according to the consensus from Tegernsee. Persistence of reflux longer than 1 s in the treated great saphenous vein was reported in 3 (6%) cases. Serious complications, such as deep vein thrombosis, pulmonary embolism, dyspnea, anaphylaxis, or neurological abnormalities, were not recorded. Conclusions : Ultrasound-guided foam sclerotherapy of incompetent great saphenous vein and varicosities with 2% polidocanol was found to be an effective and safe method of treatment during 1 year of observation. However, longer observation is necessary.